Fluid, electrolyte and early nutritional management in the preterm neonate with very low birth weight. Issue 1 (January 2021) - Goyal, Sonia; Banerjee, Sujoy
Abstract: Water and electrolytes are major constituents of the body in the preterm infant and undergo rapid changes in content and distribution within the body compartments during the first few days of postnatal adaptation. The changes can be amplified by the severity of the functional immaturity of organs and adverse environmental factors. A clear understanding of fetal physiology and postnatal adaptation, along with frequent and structured clinical assessment, is necessary to guide optimal fluid and electrolyte supplementation. An accurate fluid and electrolyte prescription is critical to delivery of optimum early nutrition. While survival of premature infants has leapt forward with widespread use of antenatal corticosteroids, postnatal surfactant and advances in respiratory support modalities, further improvement is dependent on multiple marginal gains. Meticulous attention to maintain a physiological milieu in the ex utero environment and providing high quality early nutrition to prevent catabolism and promote early growth have been shown to have a positive impact in reducing neonatal morbidities and improving long-term outcomes. This review offers a simple overview of the physiological changes during postnatal adaptation in the preterm infant. It provides practical guidance on fluid, electrolyte and nutritional management in the first few days following birth including advice about clinical assessment and preventative measures. A self-assessment exercise is also included.